Polymerization of 10,16-Dihydroxyhexadecanoic Acid, Main Monomer of Tomato Cuticle, Using the Lewis Acidic Ionic Liquid Choline Chloride·2ZnCl2 - Gómez-Patiño, Mayra Beatriz; Gutiérrez-Salgado, Diana Yaremy; García-Hernández, Edgar; Mendez-Mendez, Juan Vicente; Andraca Adame, J. Alberto; Campos-Terán, José; Arrieta-Baez, Daniel (Frontiers in Materials, 2015)
10,16-Dihydroxyhexadecanoic acid, main monomer of the tomato cuticle obtained from agroresidual wastes, was polymerized using ionic liquid (choline chloride·2ZnCl2) as catalyst at three different temperatures (80, 90, and 100°C). The resulting polyesters obtained under these conditions were insoluble in most of the organic solvents and showed different physicochemical properties. While at 80°C, polymers were obtained as powder, and at higher temperature, they were found in viscous consistency. According to the cross polarization magic angle spinning nuclear magnetic resonance and Fourier transform infrared spectroscopy attenuated total reflectance analysis, polymers showed a linear structure with an increasing degree of esterification in position C-10. Polyesters were analyzed by means of differential scanning calorimetry, atomic force microscopy, and X-ray diffraction (small- and wide-angle scattering) techniques.